A Production and operations management case study on XYZ Corporation - Francisco, Reynald (College of Engineering, 2004)
XYZ Corporation is a manufacturing company that produces various types of tin cans. Its clients are mostly involved in manufacturing a variety of products such as motor oil, cooking oil, paint biscuits, and many others. Given these products, XYZ Corporation's regular clients include Caltex Philippines, Minola Oil, Baguio Oil, Boysen, and Magic Flakes among others. Presently, the company is facing a number of problems regarding their production. Some of these problems include delays in production, high level of raw materials and work-in-process inventory, inability to meet delivery time, defectiveness of raw materials and finished goods, and tie-ups with long commitments. From the problem identification tools and techniques used, such as streamline diagnosis diagram and Ishikawa diagrams, it was determined that the major causes of the problems mentioned are the company's lack of proper production plan and proper forecasting technique. Thus, through interviews and historical obtained from the company, the study group focused mainly in developing a production plan along with a master production schedule that will help the company eliminate, or at least reduce to a minimum its current problems. Using the tools and techniques mentioned earlier, the group was able to come up with recommendations that could improve the existing production system of the company. First, the proponents recommended the use of the centered moving average technique in forecasting future demand. This technique is able to forecast demand which is within 8 absolute deviations from the actual demand. The group also recommended the use of the production plan and master production schedule to determine the number of actual machine operating hours that will produce the amount which will satisfy demand. These will also guide the company in determining the amount of uncommitted inventory for each product that they can promise to their customers. Also, from the results of the production plan made by the study group, it is recommended that the 4-hour overtime everyday be eliminated a regular 8-hour machine operation is capable enough to make the required amount of products that will satisfy demand. With the elimination of unnecessary overtime, an amount of P1406.25/day savings will be realized, and equivalently an annual savings of P421,875.00.